2003
DOI: 10.1590/s1517-83822003000100017
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection of four periodontopathogens from subgingival clinical samples

Abstract: In this study, A. actinomycetemcomitans, B. forsythus, P. gingivalis and F. nucleatum were identified from subgingival plaque from 50 periodontal patients and 50 healthy subjects. Subgingival clinical samples were collected with sterilized paper points and transported in VMGA III. From all the diluted clinical samples (1:10), DNA was obtained by boiling, and after centrifugation the supernatant was used as template. Specific primers for each bacterial species were used in PCR. PCR amplification was sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…However, in Brazil, the oral occurrence of selected periodontal pathogens is still unclear. A study conducted by Avila-Campos (2003) (7) also demonstrated a high prevalence of A. actinomycetemcomitan (70%), P. gingivalis (66%) and F. nucleatum (92%) in the healthy population made up of subjects between 18-51 years of age and 10% of blacks. Nevertheless, considering that the disease is dependent of host characteristics, we cannot affirm that the bare presence of these microorganisms represents an additional risk factor to the outbreak of the disease in the future.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in Brazil, the oral occurrence of selected periodontal pathogens is still unclear. A study conducted by Avila-Campos (2003) (7) also demonstrated a high prevalence of A. actinomycetemcomitan (70%), P. gingivalis (66%) and F. nucleatum (92%) in the healthy population made up of subjects between 18-51 years of age and 10% of blacks. Nevertheless, considering that the disease is dependent of host characteristics, we cannot affirm that the bare presence of these microorganisms represents an additional risk factor to the outbreak of the disease in the future.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, these studies also show variations that are related to the presence of periodontal pathogens in populations from different countries (7,14,22,47). Methodological factors may partially justify these discrepancies because bias of information, memory or selection might interfere with the data development.…”
Section: Introductionmentioning
confidence: 79%
“…Previous other studies evaluating the subgingival microbiota involved a considerable diversity of participants (8, 24, 25). Diversity in samples leads to a greater number of biases, but encourages the participation of a large number of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, few studies have been conducted to investigate the periodontal microbiota, most of these being conducted in the State of São Paulo (7, 8, 9, 13, 14, 15, 26). In these investigations, the bacteria P. gingivalis had its prevalence ranging from 17.8% to 90%, T. forsythia 33.3% to 100%, A. actinomycetemcomitans 23% to 90% and T. denticola was only investigated by Avila-Campos and Velásquez-Meléndez (7) with 60% of positive samples.…”
Section: Introductionmentioning
confidence: 99%
“…After centrifugation (14,000 g, 10 minutes), the supernatant was transferred to a new microcentrifuge tube and used as a control. 24 Primer sequences were obtained according to Ashimoto et al 25 (Table 1), from Invitrogen. Primers were resuspended in TE buffer (10 mM Tris-HCl pH 7.4, 1 mM EDTA pH 8.0) and stored at 220uC.…”
Section: Methodsmentioning
confidence: 99%